Anaplasma species of veterinary importance in Japan - Ybañez, Adrian Patalinghug (Vet World, 2016)
Anaplasma species of the family Anaplasmataceae, order Rickettsiales are tick-borne organisms that can cause disease in animals and humans. In Japan, all recognized species of Anaplasma (except for Anaplasma ovis) and a potentially novel Anaplasma sp. closely related to Anaplasma phagocytophilum have been reported. Most of these detected tick-borne pathogens are believed to be lowly pathogenic in animals in Japan although the zoonotic A. phagocytophilum has recently been reported to cause clinical signs in a dog and in humans. This review documents the studies and reports about Anaplasma spp. in Japan.